Specxy - Pain, Aurelia; Masri, Atiqah Syahirah; Richard, Brenda Chrysha; Ahmad Ramli, Fatin Wada'ah; Joseph, Tadia Jacinta (2017)
1.2 VISSION This company's vision is to be the widest, convenient and the most effective spectacle producer in Asia, hence, in the world.